Parents perceptions about sex education for early adolescents in primary schools in Hegarmanah village area - Rifan Muhammad Rafi; Tetti Solehati; Hendrawati, Hendrawati (Jurnal Keperawatan, 2024)
Introduction: Sex education plays an important role as a preventive measure in preventing young teenagers from reproductive health and sexuality problems. The problem in Indonesia is related to sex education, namely that parents still feel reluctant to discuss sexual topics with early teens. Objectives: This study examines to identify parents' perceptions about sex education for early adolescents in elementary schools in the Hegarmanah Village area, Jatinangor District, Sumedang Regency. Methods: This study was a descriptive quantitative study with a survey approach via questionnaires to parents of students in grades 4-6 at elementary schools in Hegarmanah Village (n=371). The sample was taken using stratified random sampling with as many as 213 respondents. Data collection used a perception questionnaire of sex education for school-age children and data analysis used univariate analysis. Results: The research results showed that the majority of respondents had a negative perception of sex education in their early teens (51.2%), while the remainder had a positive perception of sex education in their early teens (48.8%). Conclusions: The majority of parents of students in grades 4-6 in elementary schools in the Hegarmanah Village area have a bad perception of sex education. Thus, a community-based education program is needed to increase parents' perceptions of sex education to be more positive.